The Influence of Education on the Knowledge and Attitudes of Adolescents Regarding the Consumption of Ballo' Drinks in Tokke Village, Malangke District, North Luwu Regency - Idris, Fairus Prihatin; Kasman, Nirmalasari; Asrina, Andi (Window of Health : Jurnal Kesehatan, 2023)
The existence of alcoholic beverages cannot be separated from the cultural context of a society. Based on the results of observations obtained in the field in Tokke Village, Malangke District, North Luwu Regency, there were many teenagers who often drank ballo and there had been education about the use of ballo drinks. The purpose of this study was to determine the effect of education on the knowledge and attitudes of adolescents regarding the consumption of ballo drinks in Tokke Village, Malangke District, North Luwu Regency. This type of quantitative research uses a quasi-experimental research design with a one-group pretest-posttest design approach. The sampling technique in this study was purposive sampling. A total of 27 respondents were given a pre-test questionnaire before being given audiovisual media and a post-test questionnaire afterward. Data analysis used paired t-test statistics. The results showed that there was an increase in the average score of students given the intervention on the level of knowledge of adolescents from 5.66 to 7.88 and on attitude increased from 23.40 to 29.59. Then, based on the paired t-test, the effect of audiovisual media on the level of knowledge and attitudes of adolescents who drank Ballo' was obtained with a p-value of 0.000 each (p-value <0.05). Thus it was concluded that audiovisual media was able to influence the knowledge and attitudes of adolescents regarding the consumption of ballo drinks in Tokke Luwu Utara Village. For this reason, it is suggested that health workers be able to use audiovisual media to promote health and change people's behavior regarding the consumption of ballo drinks.